Sistem Scada Level Air Dalam Tangki Menggunakan PLC dan Sensor MPM4700 Intelligent Level Transmitter - Lestari, Meidi Wani (Jurnal Borneo Informatika dan Teknik Komputer, 2022)
Controlling the water level in the tank will not be a problem if it is only used for household needs. For example, if the water in the tank reaches the low level limit, you can still wait for the pump to work to be used. In contrast to the needs of water used in industry. For example, the use of water in a tank to supply water to a boiler, or a tank used in a mineral water company and others of the same type can be fatal. The use of HMI in a well-designed process industry can support high performance in an industry to produce a system that is easy to understand visually and also makes it easier for operators to handle troubleshooting problems. The availability of analog input output facilities on the PLC can read the output voltage of the water level sensor module. and display on the HMI diagram in real time